INTERKONEKSI MATA KULIAH PENDIDIKAN KEWARGANEGARAAN DENGAN BAHASA INDONESIA DALAM MEMBANGUN PEMAHAMAN MULTIKULTURAL GENERASI DIGITAL - Epin Saepudin; Asep Wawan Jatnika (Fakultas Seni Rupa dan Desain ITB, 2021)
Intolerance phenomenon that is currently happening in Indonesia requires a quick and precise response and involvesvarious parties. Universities as a miniature of the diversity of the Indonesian nation need to make a series of efforts toimprove multicultural understanding so that they can produce students who are friendly to diversity, and view differencesas a necessity as well as a gift from God. This research, conducted through library research, discusses the interconnectionbetween Pendidikan Kewarganegaraan and Bahasa Indonesia courses to build multicultural understanding of studentsliving in the digital era. The results of the research indicate that the interconnection between Pendidikan Kewarganegaraan and Bahasa Indonesia courses can be an alternative strategy to build multicultural understanding of the digital generation, especially when the substance of Bahasa Indonesia is embedded in the subject matter, i.e. the dynamics of national and state life, national identity, and integration, as well as synergies for the prosperity of the nation packaged creatively and innovatively through a digital campaign.